FAKTOR-FAKTOR YANG MEMENGARUHI MINAT BELI PANGAN ORGANIK MELALUI SITUS ONLINE - Hasrini Sari; Aditya Parama Setiaboedhi (School of Business, Bogor Agricultural University (SB-IPB), 2017)
This study is aimed to explore the factors that can increase the intention to buy and their implications in the design of marketing sites. Theoretical background used in the study is mainly adopted from the Technology Acceptance Model. Five variables are included in this research including Online Buying Intention, Ease of Use, Perceived Usefulness, Trust and Information on the Site. Data of 426 respondents were collected and analyzed using statistical methods of structural equation modeling to test the research model. The results show that the Information on the Site significantly influences Trust, and Perceived Usefulness and Trust significantly influence Online Buying Intention. Ease of Use does not significantly influence Online Buying Intention. The results of this study later become the basis for designing the information presented on a site of organic processed foods in a form of recommendations on information that should be presented on its website.Keywords: technology acceptance model, online marketing, websites, organic products, structural equation modellingAbstrakPenelitian ini bertujuan menggali faktor-faktor yang dapat meningkatkan minat beli dari pengunjung situs, serta implikasinya dalam perancangan situs pemasaran, Model utama mengadopsi Technology Acceptance Model. Empat variabel digunakan dalam penelitian ini, yaitu kemudahan penggunaan, persepsi terhadap kegunaan, rasa percaya dan informasi pada situs. Data untuk menguji model penelitian dikumpulkan dari 426 responden, dan dianalisis menggunakan metode statistik structural equation modelling. Hasilnya menunjukkan bahwa informasi pada situs berpengaruh signifikan terhadap rasa percaya. Persepsi terhadap kegunaan dan rasa percaya berpengaruh signifikan terhadap minat beli online. Kemudahan penggunaan tidak berpengaruh signifikan terhadap minat beli online. Hasil penelitian ini kemudian menjadi dasar dalam merancang informasi yang disajikan pada sebuah situs makanan olahan organik, yaitu dengan merekomendasikan informasi-informasi yang sebaiknya ditampilkan pada situs. Kata kunci: technology acceptance model, pemasaran online, situs, produk organik, structural equation modelling